Thoracolumbar meningeal fibrosis in pugs. (31st January 2020) - Rohdin, Cecilia; Ljungvall, Ingrid; Häggström, Jens; Leijon, Alexandra; Lindblad‐Toh, Kerstin; Matiasek, Kaspar; Rosati, Marco; Wohlsein, Peter; Jäderlund, Karin Hultin
Abstract: Background: Thoracolumbar myelopathies associated with spinal cord and vertebral column lesions, with a similar clinical phenotype, but different underlying etiologies, occur in pugs. Objectives: To further characterize the clinical and neuropathological characteristics of pugs with longstanding thoracolumbar myelopathy. Animals: Thirty client‐owned pure‐bred pugs with a history of more than a month of ataxia and paresis of the pelvic limbs, suggesting a myelopathy localized to the thoracolumbar spinal cord, were included in the study. Methods: Prospective clinicopathological study. Included pugs underwent a complete neurological examination and gross and histopathologic postmortem studies with focus on the spinal cord. Computed tomography (n = 18), magnetic resonance imaging (n = 17), and cerebrospinal fluid analysis (n = 27) were performed before or immediately after death. Results: Twenty male and 10 female pugs had a median age at clinical onset of 84 months (interquartile range, 66‐96). Affected pugs presented with a progressive clinical course and 80% were incontinent. There was circumferential meningeal fibrosis with concomitant focal, malacic, destruction of the neuroparenchyma in the thoracolumbar spinal cord in 24/30 pugs. Vertebral lesions accompanied the focal spinal cord lesion, and there was lympho‐histiocytic inflammation associated or not to the parenchymal lesion in 43% of the pugs. Conclusions and Clinical Importance: Meningeal fibrosis with associated focal spinal cord destruction and neighboring vertebral column lesions were common findings in pugs with long‐standing thoracolumbar myelopathy.